Paraclinical management of SARS-CoV-2 infection in paediatric patient - Ana-Maria Davitoiu; Sorina Chindris; Mirela Silvia Iancu; Iulia Tincu; Luminita Elena Spatariu; Doina Anca Plesca (Amaltea Medical Publishing House, 2020)
The world is facing, after a hundred years, a new pandemic - infection with the SARS-CoV-2 virus. Establishing a therapeutic protocol along with paraclinical infection management is the great challenge of the moment for healthcare professionals all around the world. This paper tries to stadialise the diagnosis methods and paraclinical investigations, establishing the time correspondence between this investigations and laboratory also radiological findings. The positive diagnosis of SARS-CoV-2 infection is made by using four methods of testing: RT-PCR molecular method, serological testing by chemiluminescence and ELISA, rapid tests for the determination of IgM and IgG antibodies. Laboratory findings are not disease-specific but studies have shown that lymphopenia occurs in 83% of paediatric hospitalized patients confirmed with SARS-CoV-2 infection. Imaging is not recommended for diagnosis or screening purposes in patients with suspected COVID-19, the predictive value of RT-PCR test is ten times higher than the results of pulmonary CT.